EFEKTIVITAS MODEL DEEP LEARNING DALAM MENINGKATKAN PEMAHAMAN PEMBELAJARAN BAHASA INDONESIA SISWA KELAS III SEKOLAH DASAR (STUDI KASUS DI SD INPRES 5/81 SAPPEWALIE) - karman, hasnah; Dr. Muhammad Asdar, S.Pd., M.Pd.; Muhammad Idris, S.Pd., M.Pd. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study aims to test the effectiveness of the Deep Learning (DL) model in improving the Indonesian language comprehension of third-grade elementary school students. Adopting a Qualitative Case Study method reinforced with quantitative data from learning outcomes (mixed-methods approach), the study was conducted over one month at SD Inpres 5/81 Sappewalie, involving 14 students. The implementation of the DL model proved effective, as shown by the increase in the percentage of students achieving adequate comprehension from 43% to 79% (+36%). The most significant increase (40%) was recorded in reflective skills (from 35% to 75%), followed by inferential skills (from 49% to 78%, an increase of 29%) and literal skills (from 60% to 83%, an increase of 23%). Qualitatively, DL successfully promoted active student engagement, the courage to ask questions, and the ability to connect the material with everyday contextual experiences. Despite facing challenges such as limited technological facilities and variations in student abilities, this study confirms the effectiveness of DL. The research recommendation is the need for teacher training and the use of simple learning media to optimize the implementation of the Deep Learning model. Keywords: Deep Learning , Indonesian Language Learning , Reading Comprehension , Elementary School , Learning Innovation ABSTRAK Penelitian ini bertujuan untuk menguji efektivitas model Pembelajaran Mendalam (Deep Learning/DL) dalam meningkatkan pemahaman bahasa Indonesia siswa kelas tiga sekolah dasar. Dengan menggunakan metode Studi Kasus Kualitatif yang diperkuat dengan data kuantitatif dari hasil belajar (pendekatan mixed-method), penelitian ini dilakukan selama satu bulan di SD Inpres 5/81 Sappewalie, melibatkan 14 siswa. Implementasi model DL terbukti efektif, ditunjukkan dengan peningkatan persentase siswa yang mencapai pemahaman memadai dari 43% menjadi 79% (+36%). Peningkatan paling signifikan (40%) tercatat pada keterampilan reflektif (dari 35% menjadi 75%), diikuti oleh keterampilan inferensial (dari 49% menjadi 78%, peningkatan 29%) dan keterampilan literal (dari 60% menjadi 83%, peningkatan 23%). Secara kualitatif, DL berhasil mendorong keterlibatan aktif siswa, keberanian untuk bertanya, dan kemampuan menghubungkan materi dengan pengalaman kontekstual sehari-hari. Meskipun menghadapi tantangan seperti keterbatasan sarana teknologi dan variasi dalam kemampuan siswa, penelitian ini menegaskan efektivitas model deep learning (DL). Rekomendasi penelitian ini adalah perlunya pelatihan guru dan penggunaan media pembelajaran yang sederhana untuk mengoptimalkan pelaksanaan model Deep Learning (DL) / pembelajaran inovatif. Kata Kunci: Deep Learning , Pembelajaran Bahasa Indonesia , Pemahaman Membaca , Sekolah Dasar , Inovasi Pembelajaran